Delftia acidovorans: A rare pathogen in immunocompetent and immunocompromised patients - TİGEN, ELİF; BİLGİN, HÜSEYİN; DURMUŞOĞLU, LÜTFİYE (HINDAWI LTD, 2015)
Delftia acidovorans is an aerobic, nonfermenting Gram-negative bacillus. It is usually a nonpathogenic environmental organism and is rarely clinically significant. Although D acidovorans infection most commonly occurs in hospitalized or immunocompromised patients, there are also several reports documenting the infection in immunocompetent patients. The present article describes a B cell lymphoblastic leukemia patient with D acidovorans pneumonia who was successfully treated with antibiotic therapy. The present report indicates that unusual pathogens may be clinically significant in both immunocompromised and immunocompetent patients. D acidovorans is often resistant to aminoglycosides; therefore, rapid detection of this microorganism is important.
Keywords: Delftia acidovorans; Febrile neutropenia; Immunocompromised; Pneumonia; COMAMONAS-ACIDOVORANS; BACTEREMIA; INFECTION